2016
DOI: 10.5152/dir.2016.15430
|View full text |Cite
|
Sign up to set email alerts
|

Network meta-analysis of balloon angioplasty, nondrug metal stent, drug-eluting balloon, and drug-eluting stent for treatment of infrapopliteal artery occlusive disease

Abstract: C omputed tomography (CT) colonography is a noninvasive method for colorectal carcinoma screening and was shown to be highly sensitive for colorectal cancer and polyp detection in previous studies (1-4). The major problem for diagnostic and screening CT colonography is differentiation of tumor and polyps from stool. Therefore, several methods are used for this purpose such as prone and supine imaging (looking for movement of stool), use of laxatives (to clear stool from colon), barium tagging (to mark stools w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“… 29 However, there are other meta-analyses that did not show superiority of PCB over CBA in terms of binary restenosis, TLR, and major amputation rates. 30 32 Furthermore, Katsanos et al 15 have recently showed a worse 1-year AFS rate following infrapopliteal arteries treated with PCBs, although this meta-analysis has been heavily criticized for use of nonpublished data at the time. AFS was worse in those studies using a higher dose (3.0–3.5 µg/mm 2 ) balloon drug coating and paclitaxel distal embolization was postulated to be the underlying mechanism by the authors.…”
Section: Discussionmentioning
confidence: 99%
“… 29 However, there are other meta-analyses that did not show superiority of PCB over CBA in terms of binary restenosis, TLR, and major amputation rates. 30 32 Furthermore, Katsanos et al 15 have recently showed a worse 1-year AFS rate following infrapopliteal arteries treated with PCBs, although this meta-analysis has been heavily criticized for use of nonpublished data at the time. AFS was worse in those studies using a higher dose (3.0–3.5 µg/mm 2 ) balloon drug coating and paclitaxel distal embolization was postulated to be the underlying mechanism by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Network meta-analysis is capable of aggregating the results of RCTs into a single unified analysis that compares three or more interventions while completely respecting randomization. 6,66 The advantages of network meta-analysis are the accuracy of the estimates derived from evidence integration and the accompanying relative ranking of all of the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional meta-analytical methods involve only pairwise comparisons between 2 interventions, while network meta-analysis, also known as multiple treatment comparison meta-analysis, can be used for all possible comparisons in a body of evidence regardless of whether direct head-to-head comparisons had been performed in clinical trials. 6 Therefore, a systematic review and network meta-analysis was conducted of all of the available randomized controlled trials (RCTs) that compared the efficacy of multiple treatments with regard to binary restenosis, target lesion revascularization (TLR), mortality, and technical success in the femoropopliteal segment.…”
Section: Introductionmentioning
confidence: 99%
“…α less than 0.05 was set as the significant level. The network meta‐analysis was conducted by Addis v1.16.8 (http://drugis.org/software/addis1/addis1.16) (Cipriani et al, 2009; Dias, Welton, Caldwell, & Ades, 2010; Xiao, Chen, Yang, & Kou, 2016). The software is designed according to the Bayesian hierarchical model and Markov Chain Monte Carlo (MCMC) method.…”
Section: Methodsmentioning
confidence: 99%